RETRACTED: Pyrene-Phosphonate Conjugate: Aggregation-Induced Enhanced Emission, and Selective Fe3+ Ions Sensing Properties - Sachin D. Padghan; Rajesh S. Bhosale; Sidhanath V. Bhosale; Frank Antolasic; Mohammad Al Kobaisi; Sheshanath V. Bhosale (Molecules)
A new pyrene-phosphonate colorimetric receptor 1 has been designed and synthesized in a one-step process via amide bond formation between pyrene butyric acid chloride and phosphonate-appended aniline. The pyrene-phosphonate receptor 1 showed aggregation-induced enhanced emission (AIEE) properties in water/acetonitrile (ACN) solutions. Dynamic light scattering (DLS) characterization revealed that the aggregates of receptor 1 at 80% water fraction have an average size of ≈142 nm. Field emission scanning electron microscopy (FE-SEM) analysis confirmed the formation of spherical aggregates upon solvent evaporation. The sensing properties of receptor 1 were investigated by UV-vis, fluorescence emission spectroscopy, and other optical methods. Among the tested metal ions, receptor 1 is capable of recognizing the Fe3+ ion selectively. The changes in spectral measurements were explained on the basis of complex formation. The composition of receptor 1 and Fe3+ ions was determined by using Job’s plot and found to be 1:1. The receptor 1–Fe3+ complex showed a reversible UV-vis response in the presence of EDTA.